The Presence of a Marked Imbalance Between Regulatory T Cells and Effector T Cells Reveals That Tolerance Mechanisms Could Be Compromised in Heart Transplant Children. Issue 5 (23rd April 2021) - Bernaldo-de-Quirós, Esther; López-Abente, Jacobo; Camino, Manuela; Gil, Nuria; Panadero, Esther; López-Esteban, Rocío; Martínez-Bonet, Marta; Pion, Marjorie; Correa-Rocha, Rafael
Abstract : Background: Regulatory T cells (Treg) are crucial for the induction and maintenance of graft tolerance. In pediatric heart transplant procedures, the thymus is routinely excised, removing the primary source of T-cell replenishment. Consequently, thymectomy joined to the effects of immunosuppression on the T-cell compartment may have a detrimental impact on Treg values, compromising the intrinsic tolerance mechanisms and the protective role of Treg preventing graft rejection in heart transplant children. Methods: A prospective study including 7 heart transplant children was performed, and immune cell populations were evaluated periodically in fresh peripheral blood at different time points before and up to 3 y posttransplant. Results: Treg counts decreased significantly from the seventh-month posttransplant. Furthermore, there was a significant increase in effector memory and terminally differentiated effector memory T cells coinciding with the fall of Treg counts. The Treg/Teffector ratio, a valuable marker of the tolerance/rejection balance, reached values around 90% lower than pretransplant values. Additionally, a negative correlation between Treg count and T effector frequency was observed. Particularly, when Treg count decreases below 50 or 75 cells/μL in the patients, the increase in the frequency of T effector CD4+ and CD8+, respectively, experiences a tipping point, and the proportion of T-effector cells increases dramatically. Conclusions: These results reveal that interventions employed in pediatric heart transplantation (immunosuppression and thymectomy) could induce, as an inevitable consequence, a dysregulation in the immunologic status characterized by a marked imbalance between Treg and T effector, which could jeopardize the preservation of tolerance during the period with the higher incidence of acute rejection. Abstract :